Treating Tooth Surface Loss: Adhesive Restoration of the Worn Anterior Dentition. Issue 3 (August 2016) - Patel, Mahul
The treatment of tooth surface loss (TSL) is becoming more common in primary health care and a diverse variety of patients are presenting with this condition are often being treated by general dental practitioners. This article highlights the importance of comprehensive planning and adept execution that can enhance the patient's outcome and experience. Stages of clinical planning and treatment approaches using a selection of restorative materials utilising various established adhesive clinical techniques will be presented and discussed.